Fish Analysis Containing Biogenic Amines Using Gas Chromatography Equipped With Flame Ionization And Mass Spectrometer Detectors - Muhammad Abdurrahman Munir; Ahlam Inayatullah; Hamid Alkhair Badrul (Science and Technology Indonesia, 2021)
Biogenic amines generally can be found in fish due to amines in fish undergoing a degradation process. According to the United States Food and Drug Administration (FDA), biogenic amines in fish and fish products can cause harm to consumers if consumed more than 50 µg/mL. Thus, it is important to analyze them. Five biogenic amines such as heptylamine, histamine, tyramine, cadaverine and spermidine were extracted using soaking method with methanol 50% (v/v), afterward they were detected in fish and fish products using gas chromatography – flame ionisation detector (GC-FID) and the biogenic amines structures were confirmed using mass spectrometry (MS). The detection limits (DLs) were range at 1.20 – 2.90 µg/mL. Histamine was detected in fish and fish products such as sardine (Sardinella gibosa) and mackerel (Scomberomorus guttatus) at concentration of 5.96 and 2.69 µg/mL, respectively, whereas cadaverine was found in sardine (Sardinella gibosa) at concentration of 4.96 µg/mL. Histamine concentrations in this study were detected below 50 µg/mL which is below the permissible threshold associated with scombroid poisoing.